Two sides to every tweet: Exploring the framing, predictors, and associated consequences of online shaming - Muir, Shannon Raine (Curtin University, 2023)
Online shaming, whereby individuals call out real or perceived wrongdoings online, has become an ever-increasing, global form of social policing. Despite the negative consequences associated with this phenomenon, most existing discussion and debate is anecdotal and media-based, with current understandings largely non-empirical, theoretical, and overall scarce. The overarching aim of this thesis was to explore the framing, predictors, and associated consequences of online shaming, which was achieved via a mixed-methods research project comprising four studies.